2016
DOI: 10.1186/s13054-016-1487-y
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound: a promising tool to monitor ventilator-associated pneumonia in critically ill patients

Abstract: Ventilator-associated pneumonia (VAP) is the most frequent intensive care unit (ICU)-acquired infection that is independently associated with mortality. Accurate diagnosis and timely treatment have been shown to improve the prognosis of VAP. Chest X-ray or computed tomography imaging are used for conventional assessment of VAP, but these methods are impractical for real-time measurement in critical patients. Therefore, lung ultrasound (LUS) has been increasingly used for the assessment of VAP in the ICU. Tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 59 publications
(77 reference statements)
0
40
0
3
Order By: Relevance
“…The study concluded that broader use of lung ultrasound will allow for more timely diagnosis and implementation of appropriate therapy . A meta‐analysis of published data has also shown that LUS is a valid bedside exam to diagnose and monitor VAP, especially in the intensive care setting, and reduces patients' exposure to radiation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that broader use of lung ultrasound will allow for more timely diagnosis and implementation of appropriate therapy . A meta‐analysis of published data has also shown that LUS is a valid bedside exam to diagnose and monitor VAP, especially in the intensive care setting, and reduces patients' exposure to radiation …”
Section: Discussionmentioning
confidence: 99%
“…19 A meta-analysis of published data has also shown that LUS is a valid bedside exam to diagnose and monitor VAP, especially in the intensive care setting, and reduces patients' exposure to radiation. 20 The diagnostic sign of pneumonia on ultrasound is the presence of consolidation and interstitial syndrome, which is nonspecific. 16 Consolidation, identified in most of our cases, can also be present in obstructive atelectasis.…”
Section: Discussionmentioning
confidence: 99%
“…ассоциировалось с большим количеством В-линий, чем у пациентов без гипоксемии. Подчеркнем, что увеличение количества В-линий может указывать не только на двусторонний отек легких, характерный для острого респираторного дистресс-синдрома или сердечной недостаточности, но и на развитие очаговых изменений в легких, характерных для пневмонии и ателектазирования [25][26][27]. В частности, на развитие пневмонии или ателектазирования может указывать одностороннее или ограниченное несколькими квадрантами повышение количества В-линий [28,29].…”
Section: Discussionunclassified
“…The ROC analysis showed that increased numbers of B-lines above 10 at 6 hours after completion of the surgery was predictive of the development of X-ray abnormalities at 24 hours (AUC 0.82, р = 0.02, sensitivity 86%, specificity 76%). At 6 hours after the intervention the patients who subsequently required prolonged mechanical ventilation had increased numbers of B-lines (15 [14][15][16][17][18][19][20][21][22][23][24][25][26][27]) compared to those who could be extubated within the first 24 hours after surgery (10 [3-13], p = 0.02).…”
mentioning
confidence: 99%
“…[1, [11][12][13][14] Größe des Pneumothorax [1,15] Lungenödem [16][17][18][19][20][21][22][23][24] Flüssigkeitshaushalt bei Dialysepatienten [24][25][26] Pneumonie (Lungenkonsolidierung) [23,[27][28][29] Pleuraerguss und Entlastung [30][31][32][33][34][35] Pulmonalarterienembolie [2, [36][37][38] Airway Management [39][40][41] Tracheostomie [40,42] █ VIDEO Pleuralinie zustande kommen. Sie sind parallele Wiederholungslinien der Pleura in der Tiefe, die durch die nachlassende Ultraschallenergie in der Tiefe immer schwächer werden.…”
Section: Pneumothoraxunclassified